2008
DOI: 10.1016/j.bbr.2007.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Social interactions in adolescent and adult Sprague–Dawley rats: Impact of social deprivation and test context familiarity

Abstract: Interactions with peers become particularly important during adolescence, and age differences in social interactions have been successfully modeled in rats. To determine the impact of social deprivation on social interactions under anxiogenic (unfamiliar) or non-anxiogenic (familiar) test circumstances during ontogeny, the present study used a modified social interaction test to assess the effects of 5 days of social isolation or group housing on different components of social behavior in early [postnatal day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
167
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(185 citation statements)
references
References 43 publications
13
167
5
Order By: Relevance
“…Similar profound although transient disruptive effects have been reported using aversive manipulations such as predator threat, food deprivation, physical immobilization, intense light conditions, and unfamiliarity with the play chamber: all examples of the inhibitory action of aversive states on play motivation (Klein, Padow, & Romeo, 2010;Panksepp et al, 1984;Siviy & Harrison, 2008;Siviy & Panksepp, 1985;Siviy, Harrison & McGregor, 2006;Thor & Holloway, 1984a;Vanderschuren et al, 1995;Varlinskaya & Spear, 2008) that have contributed to spread the idea that R&T is a labile and fragile behavior. Klein et al (2010) recently observed that pins and dorsal contacts disappeared in 20 min after termination of a severe stressor-30 min of physical restraint-although they returned rapidly to their normal levels after 60 min.…”
Section: Appetitive-aversive Interactions and The Fragility Of Playmentioning
confidence: 78%
See 2 more Smart Citations
“…Similar profound although transient disruptive effects have been reported using aversive manipulations such as predator threat, food deprivation, physical immobilization, intense light conditions, and unfamiliarity with the play chamber: all examples of the inhibitory action of aversive states on play motivation (Klein, Padow, & Romeo, 2010;Panksepp et al, 1984;Siviy & Harrison, 2008;Siviy & Panksepp, 1985;Siviy, Harrison & McGregor, 2006;Thor & Holloway, 1984a;Vanderschuren et al, 1995;Varlinskaya & Spear, 2008) that have contributed to spread the idea that R&T is a labile and fragile behavior. Klein et al (2010) recently observed that pins and dorsal contacts disappeared in 20 min after termination of a severe stressor-30 min of physical restraint-although they returned rapidly to their normal levels after 60 min.…”
Section: Appetitive-aversive Interactions and The Fragility Of Playmentioning
confidence: 78%
“…Yet it could be that a lack of signs of visceral upset does not necessarily imply that H and NH groups dealt with the testing procedure in the same way, as the differential impact of an unknown situation on rats' behavior in the two groups could as well depend on other factors related to familiarity (e.g., Thor & Holloway, 1984a;Vanderschuren et al, 1995;Varlinskaya & Spear, 2008). For this reason, Part 3 was conceived to evaluate whether groups with different experience (familiarization) with the play chamber would show differences in the amount of R&T, as well as whether such differences would be larger (or not) in NH groups than in H groups.…”
Section: Does Early Handling Modify the Mechanisms Of Play Motivation?mentioning
confidence: 92%
See 1 more Smart Citation
“…No significant effects were observed in the EPM (Table 2). Rats usually live in groups and have high contact with other rats to establish their social organization (Varlinskaya & Spear, 2008). The lack of physical contact generates a series of behavioral and physiological reactions that affect emotional reactivity of adult rats (Weiss et al, 2004).…”
Section: 3 Statistical Analysismentioning
confidence: 99%
“…However, previous work has paid less attention to other behavioral parameters. As social interaction encompasses different behavioral components with different functions and neurochemical circuits (Varlinskaya & Spear 2008), the effects of ovarian hormone on cocaine-induced social behavior and aggressive behavior requires further investigation.…”
Section: Introductionmentioning
confidence: 99%